Situasi Pencatatan dan Pelaporan Efek Samping Alat Kesehatan Beresiko di Rumah Sakit - Herman, Max J; Raharni, Raharni; Sasanti, Rini (Jurnal Kefarmasian Indonesia, 2009)
The incidences of adverse effects of medical device used in hospitals either as an allergic reaction, user error or as a device malﬁmction have been much revealed in mass media up to this moment. In an attempt to develop an assessment and monitoring system of risky medical device in hospitals, a study to explore the medical device adverse eﬂects in type A, B and C hospitals in four provinces (North Sumatera, DKI Jakarta, West and East Java),including psychiatric, Haji and district hospitals which were selected purposively, was carried out in 2006. Data were collected by interview using questionnaire and focus group discussion as well as direct observation. Study results show that in general the number and kind of medical devices depend on the hospital type and status. Hospital of the A type had more medical devices than type B and C hospitals. Psychiatric hospitals had just several risky medical devices, whereas educational hospitals had many more medical devices. Several adverse effects that were found and ever happened concerning the use of risky medical devices are among others the skin inﬂammation caused by overdoses in thermodermal therapy, renal inﬂammation and hematoma following the ultrasonic destruction of renal stone, depigmentation of CT scan operator facial skin and symptoms of anemia in radioisotope and X -ray operator.